Urbanisation, foraging and household food security in urban South Africa - Garekae, Hesekia (Rhodes University, Faculty of Science, Department of Environmental Science, 2020)
Over the past several decades, the world's population has been rapidly urbanising, which has resulted in a marked shift of global population from rural to urban areas. About half of the global population now reside in urban areas and is projected to increase to two-thirds by the year 2050. However, the majority of the future urban population growth is projected to be largely concentrated in Asia and sub-Saharan Africa. Despite the economic prospects normally synonymous with urbanisation, the current speed and scale of urban transformation comes with formidable challenges to contemporary urban society in these two continents. Urbanisation may presents social, economic, health and environmental challenges in urban areas, not least being a shift of the locus of food insecurity from rural to urban areas, leading to poor dietary diversity among many urban dwellers. Similarly, urbanisation alters key ecosystem services and drives habitat alteration and fragmentation, biodiversity loss, proliferation of non-native species and changes on species diversity and richness. The aforementioned changes can result in a deterioration of living conditions and decline on the quality of life for the urban dwellers. However, on the other hand, urban green infrastructure is posed as vital tool in promoting liveable cities and enhancing livelihood resilience. Against this backdrop, this study portrays wild plants, a component of urban green infrastructure, as a key resource in promoting food security and dietary diversity, thereby promoting livelihood resilience and reduced vulnerability, especially of the urban poor. Framed under the 'right to the city' approach, this study examined urban foraging practices and their potential contribution to dietary diversity and how they are shaped by and respond to urbanisation in two medium-sized South African towns. The study was conducted in the towns of Potchefstroom and Thabazimbi, South Africa. An explanatory sequential mixed method design was employed for data collection. Multi-stage sampling was employed in selecting the study participants. Firstly, the study towns were stratified into four socio-economic zones: informal, reconstruction and development programme, township and affluent. These zones resemble high density (informal, reconstruction and development programme), medium density (township) and low density (affluent) areas. Then, a total of 374 households were randomly sampled across the socio-economic zones for the main survey (Chapter 3 and 5). A subset of this sample, i.e. 72 participants was considered for dietary recalls, alongside with a random sample of 65 non-foragers (Chapter 4). An inventory of plant species available in a given foraging space was conducted from a total of 136 plots spread across different urban spaces (Chapter 2). Semi-structured interviews were conducted with a total of 81 participants (sub population of the main survey) for elucidating data on urban dynamics (Chapter 6). Lastly, complementary in-depth interviews with 46 participants were conducted. The findings showed that different urban spaces were constituted by diverse vegetation, with 262 distinct plant species encountered across the spaces. The majority (60.7%) were indigenous to South Africa. Species composition and diversity varied with space type, being significantly high in protected areas as compared to the other space types. About half (53%) of the identified plant species had at least one documented use, with medicine, food and firewood being modal, in order of frequency. Species composition and diversity differed between forageable and non-forageable species, being significantly high for forageable species. Urban foraging was widespread, about 68% of the respondents reported foraging. Foraging provided food, fuel energy, medicine, and cultural affirmation, among others. Despite the high prevalence rate of foraging, the study did not find any meaningful contribution of wild foods to overall diets. Nonetheless, wild foods demonstrated a substantial contribution in diversifying diets within particular food groups consumed such as vegetables, thus emerging essential in mitigating monotonous urban diets, particularly of the urban poor. Besides, the prevalence of foraging differed significantly between and within towns, being high for Thabazimbi (54.7%) and residents in the outskirts of town (86.2%) than Potchefstroom (45.3%) and residents in the inner part of town (33.3%). Participation in foraging was primarily a function of childhood (91.8%) exposure and experience with foraging, positive perceptions (79%) towards practice, resident in the outskirts of town (86.2%) and low household income (49.2%). The findings indicated that foraging was driven by multifaceted motivations, with culture (91.8%), health (88.7%), livelihoods needs (75.0%) and leisure (73.8%) being the most common. Vacant spaces (54.7%), riparian areas (30%), and domestic gardens (17.9%) were the most preferred foraging spaces, albeit with differences within towns. Similarly, the mean frequency of access varied with foraging spaces, being slightly high for vacant spaces than riparian areas and domestic gardens. The majority of the respondents were unaware of both formal and informal regulations managing urban landscapes, with those acknowledging some awareness falling short of articulating on the specificities of the regulations. Besides, the findings showed that foraging practice was threatened by urban transformation. Foragers perceived that the practice has changed over time, in terms of spaces, participants and regulations. There was a decreasing trend on the number and size of foraging spaces as well as shifting demographic trends of foragers. Moreover, urban transformation brought about a new set of regulations used for managing certain spaces within the urban landscape. However, some regulations prohibited or restricted access and rights to certain spaces for foraging. Hence, this prompted foragers to devise adaptation strategies to cope with the said changing dynamics. Exploring new foraging sites within and outside forager's neighbourhoods and negotiating access entry were the most frequently mentioned adaptation strategies. This study contributes to the emerging body of knowledge on urban foraging, which has being seldom understood in the Global South.
Keywords: Food sovereignty -- South Africa; Food security -- South Africa; Urban density -- South Africa; Urban agriculture -- Law and legislation -- South Africa; Sustainable urban development -- South Africa; Urban ecology (Sociology) -- South Africa; Nutrition surveys -- South Africa -- Potchefstroom; Nutrition surveys -- South Africa -- Thabazimbi; Wild plants, Edible -- South Africa